(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Vehicular Ad-hoc Networks (VANETs), a type of Internet of Things system, allow groups of cars to communicate with one another and with traffic monitoring devices, improving traffic safety and quality of life. In a VANET, vehicles are used by drivers and the system controller to report not only their own status but also that of the road, traffic, and environment. Since VANET networks are open to the public, there is a significant influx and outflow of automobiles. This feature has led to the emergence of two top-tier requirements for VANET security: first, that systems ensuring message security must be quick, and second, that vehicles in a VANET must be held responsible for the accuracy of the information they provide. This study proposes an efficient pairing-free signature technique for VANETs that protects against signer identity fraud, even in situations of insider attacks, without the need for a tamper-proof device.